Rehabilitation & resilience: a mediation between landscape & society - Moyo, Verney K W (My University, 2021)
This thesis is centred around 2, pivotal questions. Firstly, what is architecture’s agency in the rehabilitation of troubled landscapes, and secondly, how can it retain agency past this initial remit. We live in an age where the planet is threatened by climate change and other man-made environmental disasters, an age of consumerism where few things remain untouched by capitalist centred materialisms. By designing a structure/structure of systems that challenges broken landscapes this research poses the idea that we have a chance of stopping our steady march toward the brink of oblivion – indeed, perhaps even to turn back the hands of time to right some of the ecological harm we have already effected; often for economic gain. As such, the choice of site in the exploration of this statement was both poignant and pivotal: an abandoned belt of gold fields lying just south of the Johannesburg CBD. The area – as outlined in this study - is a roiling powder keg of conflicting sentiments and ideas, and a most potent embodiment of the consequences of vice and economic greed one can find anywhere in the world. From it come questions of how society has come to interact with landscape, questions of extraction, of usage, and re-usage, of exploitation and reciprocation. By acknowledging buildings as the main avatars/ mediums/ and conduits through which we converse with landscape, this thesis will posit the design of such a structure that will serve as an austere critique of the current status-quo within the Witwatersrand mining area while simultaneously setting a brighter, more sustainable precedent for the coming years. A common theme in the structuring of this particular narrative, we will be forever trying to search for golden mean, a steady middle-way between vying extremes in everything we investigate and propose. Towing the line between the fantastical, the futuristic and the eminently grounded and practical, between the extreme and the mundane, this thesis will attempt to cover as many bases and theories as fiscally possible within a year of study. Through this process of data distillation and refinement will our final structure be born
A thesis submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Masters of Architecture (Professional), 2021